2021
DOI: 10.1186/s12864-021-08125-9
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype-tissue expression and exploration (PTEE) resource facilitates the choice of tissue for RNA-seq-based clinical genetics studies

Abstract: Background RNA-seq emerges as a valuable method for clinical genetics. The transcriptome is “dynamic” and tissue-specific, but typically the probed tissues to analyze (TA) are different from the tissue of interest (TI) based on pathophysiology. Results We developed Phenotype-Tissue Expression and Exploration (PTEE), a tool to facilitate the decision about the most suitable TA for RNA-seq. We integrated phenotype-annotated genes, used 54 tissues fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
2
12
0
Order By: Relevance
“…This revealed that there are four genes with high expression in brain cortex (Supplementary Fig. S1 14 ): FAN1, MTMR10, KLF13, OTUD7A , all of which showed significant down-regulation in blood (Supplementary Table S1) of our subjects, as well as mouse brain cortex, confirming that a gene dosage effect of the microdeletion contributes to the transcriptional dysregulation. Other genes included in the typical deletion region: TRPM1, CHRNA7, MIR211, ARHGAP11B , display low expression levels in brain cortex and blood (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This revealed that there are four genes with high expression in brain cortex (Supplementary Fig. S1 14 ): FAN1, MTMR10, KLF13, OTUD7A , all of which showed significant down-regulation in blood (Supplementary Table S1) of our subjects, as well as mouse brain cortex, confirming that a gene dosage effect of the microdeletion contributes to the transcriptional dysregulation. Other genes included in the typical deletion region: TRPM1, CHRNA7, MIR211, ARHGAP11B , display low expression levels in brain cortex and blood (Supplementary Fig.…”
Section: Discussionsupporting
confidence: 63%
“…S1). Four genes have an expression higher than 1.5 TPMs in brain cortex 14 ( FAN1, MTMR10, KLF13, OTUD7A ) of which MTMR10 and KLF13 are also highly expressed in blood (Supplementary Fig. S1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations